1962
DOI: 10.1172/jci104545
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF CHRONIC HEPATIC VENOUS CONGESTION ON THE METABOLISM OF d,l-ALDOSTERONE AND d-ALDOSTERONE*

Abstract: In 1950 Deming and Luetscher demonstrated increased salt-retaining activity in urine from patients with congestive heart failure (1). In 1953 aldosterone was isolated (2), and subsequently the urinary excretion of this hormone was found to be elevated in nearly all the clinical states associated with edema. Two possible mechanisms could lead to an increase in the plasma level of aldosterone and thus to an increase in urinary aldosterone excretion: 1) hypersecretion of aldosterone, and 2) a decreased rate of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1964
1964
1992
1992

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…In an earlier study (1), the rate of metabolism of aldosterone was found to be decreased in dogs with chronic passive congestion of the liver secondary to thoracic inferior vena caval constriction. After hepatectomy of these animals and of normal dogs, the metabolism of aldosterone was almost abolished.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In an earlier study (1), the rate of metabolism of aldosterone was found to be decreased in dogs with chronic passive congestion of the liver secondary to thoracic inferior vena caval constriction. After hepatectomy of these animals and of normal dogs, the metabolism of aldosterone was almost abolished.…”
mentioning
confidence: 79%
“…The concentration of HW-d-aldosterone was measured in peripheral venous plasma by a slight modification (1) of the double isotope derivative assay (8), and two additional changes were made for the present study. First, the samples were run through a third chromatography; a cyclohexane (100 parts), benzene (50 parts), methanol (100 parts), and water (25 parts) system was used, and the chromatogram was developed for 10 hours.…”
Section: Methodsmentioning
confidence: 99%
“…[ 13] In addition to M., the three other quantities yielded uniquely by the compartment analysis are obtained from equations 1, 2, 10 as (14-17) [14] [ Eb/MOA = n(1 -u) [10] [26] [27] [28]…”
Section: Discussionmentioning
confidence: 99%
“…Soiva, Haskins, and McCafferty showed the rapid disappearance of plasma radioactivity after the injection of 276 jug progesterone-4-14C (11). Nine minutes after the single injection of progesterone-4-14C Zander showed the presence in the plasma of pregnanolone (5,8 pregnane 3a-ol, 20-one), pregnanediol (5,8 pregnane 3a-20a-diol), and 20a-hydroxy-4 pregnen, 3-one). Short and Eton (12) calculated tj to be 5 minutes in pregnant women after the removal of the placenta at Cesarean section.…”
Section: (3)mentioning
confidence: 98%